Determination of Effective Policies for Ecological Agriculture Development with System Dynamics and Agent Based Models – Case Study in Slovenia - Rozman, Črtomir; Škraba, Andrej; Pažek, Karmen; Kljajić, Miroljub; Bavec, Martina; Bavec, Franci (IntechOpen, 2011)
None